Comparison of Genus Specific PCR and Culture with or without Sonication for Microbiological Diagnosis of Vascular Graft Infection. (October 2018) - Puges, Mathilde; Pereyre, Sabine; Bérard, Xavier; Accoceberry, Isabelle; Le Roy, Chloé; Stecken, Laurent; Pinaquy, Jean-Baptiste; Desclaux, Arnaud; Dupon, Michel; Bébéar, Cécile; Cazanave, Charles
Abstract : Objectives: Vascular graft infections (VGIs) are severe and require prolonged adequate antimicrobial therapy. However, up to 45% of conventional cultures are negative. Sonication and genus specific PCRs for microbiological diagnosis of VGI was evaluated. Methods: Samples were prospectively obtained from explanted vascular grafts in Bordeaux University Hospital. Conventional bacterial cultures with and without prior sonication of samples were performed. A genus specific PCR assay panel, targeting the most frequent bacteria involved in VGI ( Staphylococcus, Streptococcus, Enterococcus, and Enterobacteriaceae), was also applied to sonicate fluids. The performance of these three diagnostic strategies was compared. Results: Forty-five patients (118 samples) were included between July 2014 and October 2015. Six patients had no infection and 39 had a VGI. Sensitivities of graft culture, sonicate fluid culture, and genus specific PCR were 85.7%, 89.7%, and 79.5%, respectively. Specificities were 100%, 100%, and 83.3%, respectively. Sonicate fluid culture was positive for five graft samples (from four patients) with negative culture without sonication. Four VGIs were detected by PCR only (3 patients had previously received antibiotics). For 15 patients with positive graft cultures, PCR identified at least one additional bacterium compared with culture, thus 30 additional bacteria for all included patients. By combining sonicate fluid culture and PCR, a microbiological diagnosis was obtained for all patients with VGI. Conclusions: There was no statistical difference between performances of culture with and without sonication and genus specific PCR. However, combining sonicate fluid cultures and PCR may be the best strategy for microbiological diagnostic of VGI.